Pelatihan Dan Pengenalan Design Grafis Dengan Menggunakan Aplikasi Paint Untuk Siswa/i SMP Utama Pondok Aren Tangerang Selatan - Somantri; Fachul Rozi; Muhammad Abdillah; Abdul Rizal Kholiq; Akmal Firmansyah; Ilham Bimantoro; Aditya Rafi Pratama; Sahnaya Bunga Firdausy; Fajar Hikmatullah (CV. Multi Kreasi Media, 2025)
This training aims to enhance the skills of students at SMP Utama Pondok Aren, Tangerang Selatan, in using the Paint application, which is a built-in Microsoft software. By utilizing Paint, students are expected to develop basic drawing and graphic design skills, which can serve as a crucial foundation in learning information and communication technology. The training methods include theoretical and practical sessions, where students are introduced to various features and functions of the Paint application. Evaluation is conducted through the assessment of practical assignments given during the training. The results of the training indicate a significant improvement in students' understanding and skills in using the Paint application. This program is expected to make a positive contribution to the efforts of developing technological skills among junior high school students.